Dampak Pemasaran Digital Dan Promosi Terhadap Pengembangan Usaha Mikro Kecil Menengah (UMKM) Di Kecamatan Pekalongan Lampung Timur - Nanda Andreas Octavini; Durotun Nasikah (Jurnal Manajemen DIVERSIFIKASI, 2025)
This study aims to determine the impact of digital marketing and promotion on thedevelopment of MSMEs in Pekalongan District, East Lampung. The research uses aquantitative descriptive approach with a sample of 50 respondents. The analysis techniqueemployed in this study is multiple linear regression analysis. The results of the study indicatethat:(1) Digital marketing has a significant influence on the development of MSMEs,(2) Promotion has a significant influence on the development of MSMEs, and(3) Digital marketing and promotion simultaneously influence the development of MSMEs